2014
DOI: 10.1089/bari.2014.0024
|View full text |Cite
|
Sign up to set email alerts
|

Routine Screening Endoscopy before Bariatric Surgery: Is It Necessary?

Abstract: Background: Routine esophagogastroduodenoscopy (EGD) prior to bariatric surgery has not been consistently shown to change the management of the patient. A study was performed to estimate the proportion of patients undergoing bariatric surgery evaluation who had abnormal findings on preoperative EGD that resulted in alteration of management and, second, to evaluate potential risk factors for occurrence of abnormal findings on the EGD. Methods: An observational, retrospective study in which all 232 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…In general, prospective studies that implemented pre-operative endoscopy demonstrated changes the surgical treatment in about 2-3 % of cases. Additionally, the information obtained did alter the medical management for GERD in approximately 50 % [7,8]. In our case, it is possible that a pre-operative endoscopy would have revealed a specific pathology such as a stricture that could have led to a subsequent injury, but the lack of symptoms suggests that this is just speculative.…”
Section: Discussionmentioning
confidence: 77%
“…In general, prospective studies that implemented pre-operative endoscopy demonstrated changes the surgical treatment in about 2-3 % of cases. Additionally, the information obtained did alter the medical management for GERD in approximately 50 % [7,8]. In our case, it is possible that a pre-operative endoscopy would have revealed a specific pathology such as a stricture that could have led to a subsequent injury, but the lack of symptoms suggests that this is just speculative.…”
Section: Discussionmentioning
confidence: 77%
“…Published guidelines from the European Association for Endoscopic Surgery (EAES) in 2005 and the American Society of Gastroenterology (ASGE) in 2008 recommended that upper gastrointestinal endoscopy should be performed in all symptomatic patients undergoing bariatric surgery, and considered in all candidates [1,2]. However, the rationale for using routine endoscopy in asymptomatic patients before bariatric surgery remains contentious [3][4][5][6][7][8][9][10]. Several authors have now documented the lack of correlation between patient symptoms and endoscopic findings and have suggested that routine preoperative endoscopy might in fact be useful in detecting both lesions and inflammation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended by several specialty societal guidelines, even in asymptomatic patients, to detect upper gastrointestinal abnormalities. (29)(30)(31)(32)(33) We used a 36 Fr bougie for sizing of the gastric sleeve. Marceau used a 60 Fr.…”
mentioning
confidence: 99%